2014
DOI: 10.1016/j.jinorgbio.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Insights into redox sensing metalloproteins in Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis, the pathogen that causes tuberculosis, has evolved sophisticated mechanisms for evading assault by the human host. This review focuses on M. tuberculosis regulatory metalloproteins that are sensitive to exogenous stresses attributed to changes in the levels of gaseous molecules (i.e., molecular oxygen, carbon monoxide and nitric oxide) to elicit an intracellular response. In particular, we highlight recent developments on the subfamily of Whi proteins, redox sensing WhiB-like protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 121 publications
0
21
0
Order By: Relevance
“…The major antigens ESAT-6 and CFP10 are secreted by the ESX-1 secretion system of M. tuberculosis, a system which has been implicated in mycobacterial escape from the phagosome to the cytosol that results in a Type-I interferon response within the infected macrophage (57, 68, 69). PhoP and EspR regulate the expression of ESX-1 secretion system-related genes and as stated are significantly associated with the DE genes between the two pathogens; despite EspR being expressed to a higher level in M. tuberculosis (Supp_III.xlsx), there is a significant upregulation of the ESX-1 secretion system in M. bovis in comparison to M. tuberculosis, including ESX-1-related proteins such as EsxA, EspA, EspC, EspD at both the transcriptional and translational level (55-57, 70, 71) (Fig.2B). Furthermore, PhoP was expressed to a higher level in M. bovis; this may represent an attempt at a compensatory mechanism for aberrant PhoP signalling and supports previous reports of suboptimal PhoP signalling in M. bovis (23, 59).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major antigens ESAT-6 and CFP10 are secreted by the ESX-1 secretion system of M. tuberculosis, a system which has been implicated in mycobacterial escape from the phagosome to the cytosol that results in a Type-I interferon response within the infected macrophage (57, 68, 69). PhoP and EspR regulate the expression of ESX-1 secretion system-related genes and as stated are significantly associated with the DE genes between the two pathogens; despite EspR being expressed to a higher level in M. tuberculosis (Supp_III.xlsx), there is a significant upregulation of the ESX-1 secretion system in M. bovis in comparison to M. tuberculosis, including ESX-1-related proteins such as EsxA, EspA, EspC, EspD at both the transcriptional and translational level (55-57, 70, 71) (Fig.2B). Furthermore, PhoP was expressed to a higher level in M. bovis; this may represent an attempt at a compensatory mechanism for aberrant PhoP signalling and supports previous reports of suboptimal PhoP signalling in M. bovis (23, 59).…”
Section: Resultsmentioning
confidence: 99%
“…The PhoPR two-component system is important for M. tuberculosis infection and it has been suggested that mutations in PhoR attenuate animal-adapted M. bovis in humans (23, 99-105). PhoP regulates the production of virulence associated cell wall lipids and controls the expression of EspA, an ESX-1 secretion pathway related protein involved in the secretion of the major antigen EsxA/ESAT6 (55, 56, 70, 71). We found that the ESX-1 secretion system is expressed to a higher degree at both the RNA and protein level in M. bovis in comparison to M. tuberculosis; differences in ESX-1 secretion system expression between the two pathogens may be a consequence of a SNP in the promoter of the whiB6 gene in M. tuberculosis H37Rv or attributed to attenuated PhoPR signalling in M. bovis (56).…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive response of M. tuberculosis to hypoxia has been the subject of intense investigation and has been shown to comprise both transient and enduring components (35). The former is associated with the induction of an ϳ47-gene regulon, controlled by the DosR/DosS/DosT two-component system, which also is induced by CO and NO (36). A key feature of the DosR response is the upregulation of the narK2-encoded nitrate transporter, which results in elevated NR activity under hypoxic conditions (37).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, reduction with S 2 O 4 2Ϫ (E°ϭ Ϫ660 mV) (64) causes a ligand switch from Cys-92 to His-95. Such behavior representing an activation/de-activation switch is well established for a number of other heme sensory proteins with very distinct folds (Table 3) (3,59,65).…”
Section: Discussionmentioning
confidence: 67%